Implementation of 3-dimensional parcel for management corporation in strata scheme / Siti Nuranissa Eraman - Eraman, Siti Nuranissa (2019)
The implementation of visualization in 3-dimensional building in cadastral strata survey environment is still considered to be low in Malaysia. The aim of this study is to improve strata management in management corporation (MC) of strata scheme that is related to 3-dimensional building. In this study, the data of this survey are refer to the building plan and, other relevant information that is helpful in this study. Next, in this survey the analysis that will be achieved and it can be viewed in 3-dimensional modelling. The analysis can be made in two way based on the objective that need to be achieved. First analysis in building for 3-dimensional modelling is in the visualization of the modelling which can be view in 3-dimensionaI and for the second analysis is how strata management can help in managing the information for management corporation (MC). The findings from this study show that the 3-dimensional parcel modelling using AutoCAD, SketchUP, ArcGIS software with the information from building plan to build the modelling in 3-dimensional. In conclusion, the implementation of 3-dimensional in cadastral strata survey may improve management in cadastral environment in Malaysia.